Circunferência de cintura e ácido úrico em mulheres com e sem síndrome metabólica - Silva, Gilberto Reis Agostinho (2019)
The metabolic syndrome is characterized by a set of risk factors for the development of cardiovascular diseases, which are generally more concomitant than isolated, and are related to obesity (particularly central). There is evidence of a relationship between increased serum uric acid levels and altered metabolic syndrome components, as well as the metabolic syndrome itself. Therefore, the objective proposed in the present thesis was to analyze the alteration of this biomarker in the plasma and salivary fluid of women with and without metabolic syndrome. For that, the uric acid levels alterations were evaluated in 164 women with and without the presence of metabolic syndrome, aged 20 to 78 years, attended by the Family Health Program (FHP) in the city of Santo Antônio de Goiás. metabolic syndrome was identified according to the diagnostic criteria established by the NCEP - ATP III, however, IDF (International Diabetes Federation) criteria were used to compare the variables. The variables evaluated were abdominal circumference, fasting blood glucose, HDL-cholesterol concentration, triglycerides and uric acid of the blood and saliva, in addition to blood pressure measurement. Data were analyzed using the statistical package SPSS (Statistical Package for Social Science), version 23. The level of significance was set at 5% (p <0.05). The characterization of the sample was performed by means of absolute and relative frequency for categorical variables and median, mean, standard deviation and interquartile ranges for continuous variables. The Shapiro-Wilk test was used to evaluate the normality of all dependent variables. In order to compare the mean values between the CC categories, the Student t test (with Levene test for equality of variance) or the Mann-Whitney U test were applied in the data with a normal or non-normal distribution in both categories . The chi-square test was used to evaluate the association between the classification of AUP and AUS with the exploratory variables. Normality of the quantitative data was verified by applying the Kruskal-Wallis test. The Mann-Whitney or Kruskal-Wallis test in the comparison of the mean values of the AUP and AUS with the exploratory variables. Spearman's correlation was used to verify the relationship between AUP and AUS values. Multiple linear regression was also performed with the AUP and AUS values with the exploratory variables. Increased waist circumference (≥ 80 cm, IDF or> 88 cm, NCEP-ATPIII) showed a significant correlation with systolic blood pressure, diastolic blood pressure, glucose, HDL cholesterol, and triglycerides. When participants were distributed by age, stronger correlations were observed with the dependent variables mentioned above. In the bivariate linear regression analysis with dichotomized health risk factors as dependent variable and increased waist circumference as an independent variable, about 63.0% of the variability of the increase in systolic blood pressure (≥ 130 mmHg) in the age group of 20 to 40 years was predicted by increased waist circumference according to both criteria. There was a significant association with age (p 0.01), systolic hypertension (p 0.05) and HDL cholesterol (p 0.03), in relation to elevated levels of plasma uric acid (AUP). The same was not evidenced when salivary uric acid (AUS) was used. It was observed that, even though there was no significant difference, both mean values of AUP and AUS were higher in women with confirmation of MS. When analyzing age as an exploratory variable, we found a significant difference in relation to AUS and the different age groups (p 0.01), where the values increased proportionally to the increase in age. When CC was analyzed, a significant difference was identified between this component of MS and AUP (p 0.01). Based on the study, it was possible to conclude that waist circumference above 80 cm in adult women aged 20 to 40 years predicted strongly the variability in altered systolic blood pressure, noting the importance of waist circumference measurement in monitoring and prevention of cardiovascular and metabolic diseases in women in this age group. It is also concluded that uric acid directly influences some of the components of MS, such as waist circumference, systolic blood pressure and HDL cholesterol, as well as the metabolic syndrome itself, although it did not find a significant difference when related to UA and SM, it was observed that individuals with MS presented higher levels of uric acid.